ANALYSIS OF THE Z WELL PRODUCTION TEST USING THE HORIZONTAL LIP PRESSURE METHOD AT PT. PERTAMINA GEOTHERMAL ENERGY ULUBELU AREA - Akhmad Sofyan; Yoga Dwi Guna Bujang; Dhea Cittameyulfa Dewi (Indonesian Journal of Energy and Mineral, 2023)
The Ulubelu area of PT. Pertamina Geothermal Energy is a geothermal field that produces two-phase hot fluids with water domination and has a generation capacity of 2 x 110 MW. The production well fluids are conveyed to a separator and scrubber before being directed to the power generation unit (PLTP). Prior to production, a well production test is necessary to determine the well's condition, reservoir characteristics, production capacity, and enthalpy contained in the well fluids. This activity is carried out after drilling and completion testing have been conducted. The method used in testing the Z well is the horizontal lip pressure method developed by Russell James. The purpose of this production test is to determine the maximum and optimum production by adjusting the throttle valve opening in various ways so that the supplied fluid amount matches the PLTP conditions. The production test yields data in the form of parameters to be processed, such as dryness fraction, fluid mass flow rate, enthalpy, and generation. From this data, a deliverability curve can be generated in the form of a graph that shows the well's production capacity at different wellhead pressures.